Peripheral Ulcerative Keratitis with Pyoderma Gangrenosum - Adrián Imbernón-Moya; Elena Vargas-Laguna; Antonio Aguilar; Miguel Ángel Gallego; Claudia Vergara; María Fernanda Nistal (Hindawi Limited, 2015)
Pyoderma gangrenosum is an unusual necrotizing noninfective and ulcerative skin disease whose cause is unknown. Ophthalmic involvement in pyoderma gangrenosum is an unusual event. Only a few cases have been reported, from which we can highlight scleral, corneal, and orbital cases. Peripheral ulcerative keratitis is a process which destroys the peripheral cornea. Its cause is still unknown although it is often associated with autoimmune conditions. Pyoderma gangrenosum should be included in the differential diagnosis of peripheral ulcerative keratitis. Early recognition of these manifestations can vary the prognosis by applying the appropriate treatment. We introduce a 70-year-old woman who suffered pyoderma gangrenosum associated with peripheral ulcerative keratitis in her left eye. The patient's skin lesions and peripheral keratitis responded successfully to systemic steroids and cyclosporine A.